A three-dimensional model for rain-wind induced vibration of stay cables in cable-stayed bridges - Truong, Viet Hung (2020)
In this paper, the effects of wind velocity according to height above the ground on the rain-wind induced vibration (RWIV) of stay cables are investigated. RWIV of the cable is modeled using the linear theory of cable vibration and the central difference algorithm. The wind speed profile according to height above the ground, which affects both aerodynamic forces acting on the cable and the oscillation of the rivulet on the cable surface, is taken into account in the theoretical formulation. The fourth-order method Runge-Kutta is used for solving the system of differential equation of the cable oscillation. The proposed 3D model of the stay cable is then used to assess the effects of wind velocity distribution on cable RWIV. The results obtained in this study showed that in most current cable-stayed bridges, in which the height of pylons is lower than 200 m, the change of wind velocity according to the height above the ground should be included in RWIV analyses.